PENGARUH TATA KELOLA RISIKO PERUSAHAAN PADA KINERJA PERBANKAN DI INDONESIA - Risa Dwi Prameswari; Wahyu Meiranto (Diponegoro Journal of Accounting, 2019)
This research aims to examine the effect of risk governance on bank’s performance that was on Indonesia Stock Exchange’s listed in 2016-2017. In addition, this research also examine whether the risk disclosure, number of risk committee that will effect the bank’s performance in a more complete and more detailed. The population in this research were several bank companies listed on Indonesia Stock Exchange (IDX) in Indonesia in 2016 and 2017. Then 75 samples were obtained from 90 populations registred on the IDX. The analytical tool used in this research is multipled regression analysis. The result of this examine show that risk disclosure has a positive significant effect to bank’s performance and the number of the committee will not effect the bank’s performance. With this result, it can conluded that risk disclosure increase the bank’s performance. And the number of committee, maybe it is influenced by other factors.